Clinical and molecular features of patients with amyotrophic lateral sclerosis and SOD1 mutations: a monocentric study - Gagliardi, Delia; Ripellino, Paolo; Meneri, Megi; Del Bo, Roberto; Antognozzi, Sara; Comi, Giacomo Pietro; Gobbi, Claudio; Ratti, Antonia; Ticozzi, Nicola; Silani, Vincenzo; Ronchi, Dario; Corti, Stefania (Frontiers in neurology, 2023)
was the first gene associated with both familial and sporadic forms of amyotrophic lateral sclerosis (ALS) and is the second most mutated gene in Caucasian ALS patients. Given their high clinical and molecular heterogeneity, a detailed characterization of -ALS patients could improve knowledge about the natural history of this disease. Here, the authors aimed to provide a clinical and molecular description of a monocentric cohort of -ALS patients. Amyotrophic lateral sclerosis (ALS) patients referring to the neurology unit of our center between 2008 and 2021 were clinically assessed and underwent molecular testing for . Segregation studies in available family members and analysis were performed to sustain the pathogenicity of the identified variants. Among the 576 patients in our cohort, we identified 19 individuals harboring a mutation in (3.3%), including 15 (78.9%) with a familial and four (21.1%) with a sporadic form. The spinal onset of the disease was observed in all patients, and survival was extremely variable, ranging from 8 months to over 30 years. Twelve different missense variants were identified in our cohort, including one novel mutation (p.Pro67Leu). In the present series, we provided the first description of an Italian monocentric cohort of -ALS patients, and we expanded the repertoire of mutations. Our cohort presents several remarkable features, including variable expressivity in the same family, atypical presentation (ataxia, cognitive impairment, and other extra-motor symptoms), and different modes of inheritance of a given mutation in the same family. Given the recent authorization of -directed antisense oligonucleotide for use in -ALS patients, we recommend prompt screening for mutations in novel ALS patients with familiar or sporadic presentations.